SCHIZOPHRENIC AUDITORY AND VISUAL HALLUCINATIONS IN THE POEM “DU PYEON-EUI JUGEUM” - Istirahmah, Nadira; Panggabean, Lovelyta; Latifah, Eva (UI Scholars Hub, 2021)
Although the mental health issue is often brought up as an interesting discussion topic for these past few years, negative stigmas towards people with psychological disorders, especially schizophrenia, still exist within society. However, by expressing self-acceptance and innermost thoughts in her poetry, Choi Seung-Ja succeeded in breaking the stigmas and lived her life as a schizophrenic poet. Based on this fact, this research aims to unfold the meaning of the auditory and visual hallucinations shown in Choi Seung-Ja’s poem entitled “Du Pyeon-eui Jugeum” and to explain the motives behind the creation of the schizophrenic aspects. In order to achieve these goals, this research was carried out in three stages: reading stage; reconciliation stage; interpretation stage, through expressive psycho-literary approach. The result was obtained by associating the poem’s sensory imageries with theories related to schizophrenia disorder, the poet’s life history, and historical events. The findings show that “Du Pyeon-eui Jugeum” reflects Choi Seung-Ja’s notion which doesn’t portray death merely as a beginning of destruction but also as a gateway to self-restoration and catharsis. Furthermore, hallucinations were used not only to develop the poem’s imageries but were also used to project the feelings and the external aspects of the poet.